Braids & buns, ponies & pigtails : 50 hairstyles every girl will love - Strebe, Jenny (Chronicle Books, 2016)
This essential resource for little girls and their parents features 50 fun styles to wear to school, parties, and playdates. Each style is accompanied by chic photography, easy-to-follow illustrations, and cross-references to other similar styles to try. This comprehensive guide also includes tips for junior hair care and advice on accessories such as clips and ribbons. From a Minnie Mouse bun for a themed birthday party to a French braid perfect for trampolining with friends, Braids & Buns, Ponies & Pigtails includes all the information parents need to create pretty styles any little girl will love.-- From publisher.